Análisis y estudio de factibilidad para implementación de la norma iso 9001 en la empresa red-nueva conexión s.a.s - Suarez Mina, Luis Leonel (2022)
This research project is descriptive and focuses on the analysis and study for the implementation of the ISO 9001 Standard in the company Red Nueva Conexión of the San Francisco de Puebloviejo Canton of the Los Ríos Province. The purpose of this research is to improve and optimize the quality processes of the company and to help improve the quality of service to its customers. The population that was taken to carry out the survey is fourteen clients, among whom seven are old and seven are new, with this small sample that was taken as a reference, it is intended to know the general opinion of all the clients of the company. With the results obtained from the respondents, an analysis was carried out, which served to give conclusions and recommendations to the company Red Nueva Conexión. The results obtained in the survey helped to demonstrate the shortcomings that the company has, among these the ones that stand out the most are the lack of efficiency and agility of the collaborators and the urgent improvement of service quality; That is why it was considered that in the company it is necessary to implement the ISO 9001 Standard, which will help improve the quality of the processes and customer service.